(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: The aim of this study was to assess the ready-to-eat food samples available in Kathmandu and detect if Bacillus cereus were present. Methods: A cross sectional study comprising of field and laboratory was conducted in Kathmandu, Nepal. A total of 240 ready-to-eat food samples were collected from February 2021 to January 2022 covering different food outlets of Kathmandu. The food samples were grouped into three main categories- rice, bakery, and dairy. The homogenate mixture of sample was prepared. The samples were processed following the standard microbiological procedures and Bacillus cereus was identified by different biochemical tests. Results: Out of 240 samples analyzed, 40% samples showed the presence of Bacillus cereus which was most prevalent in bakery items followed by rice and dairy items (50%, 42.5%, and 28% respectively). One of the Bacillus cereus isolates was emetic toxin-producing type as detected from the phenotypic analysis. The contamination of Bacillus cereus ranged from 1.64 to 6.83 log cfu/g and 20.8% of the samples were potentially hazardous (>5 log cfu/g). Conclusion: This study reports relatively high prevalence of Bacillus cereus in ready-to-eat food samples indicating a serious public health concern. There may be a likely connection between the standards maintained during preparation, packaging, storage, and transport; and regular monitoring of ready-to-eat food items is imperative to prevent any food poisoning incidences.